Surpassing the repeaterless bound with a photon-number encoded measurement-device-independent quantum key distribution protocol - Erkilic, Ozlem; Conlon, Lorcan; Shajilal, Biveen; Kish, Sebastian; Tserkis, Spyros; Kim, Yong-Su; Lam, Ping Koy; Assad, Syed M. M. (The University of New South Wales (UNSW Australia) | Nature Publishing Group, 2023)
Decoherence is detrimental to quantum key distribution (QKD) over large distances. One of the proposed solutions is to use quantum repeaters, which divide the total distance between the users into smaller segments to minimise the effects of the losses in the channel. Here we introduce a measurement-device-independent protocol which uses high-dimensional states prepared by two distant trusted parties and a coherent total photon number detection for the entanglement swapping measurement at the repeater station. We present an experimentally feasible protocol that can be implemented with current technology as the required states reduce down to the single-photon level over large distances. This protocol outperforms the existing measurement-device-independent and twin-field QKD protocols by achieving better key rates in general and higher transmission distance in total when experimental imperfections are considered. It also surpasses the fundamental limit of the repeaterless bound at a much shorter transmission distance in comparison to the existing TF-QKD protocols.